(untitled) - Cram, Catherine (Indianapolis, IN, 2007)
Understand how a fit pregnancy helps with delivery and postpartum shape-up. From yoga and swimming to weight training and aerobics, you'll see how to get started with a fun, step-by-step fitness routine. Plus, you get expert advice on activities to avoid as well as staying motivated during and after your pregnancy.
Keywords: Physical fitness for pregnant women,Thể dục cho phụ nữ mang thai